North European comparison of treatment strategy and survival in older patients with resectable gastric cancer: A EURECCA upper gastrointestinal group analysis. Issue 12 (December 2018) - Claassen, Y.H.M.; Dikken, J.L.; Hartgrink, H.H.; de Steur, W.O.; Slingerland, M.; Verhoeven, R.H.A.; van Eycken, E.; de Schutter, H.; Johansson, J.; Rouvelas, I.; Johnson, E.; Hjortland, G.O.; et al.
Abstract: Background: As older gastric cancer patients are often excluded from randomized clinical trials, the most appropriate treatment strategy for these patients remains unclear. The current study aimed to gain more insight in treatment strategies and relative survival of older patients with resectable gastric cancer across Europe. Methods: Population-based cohorts from Belgium, Denmark, The Netherlands, Norway, and Sweden were combined. Patients ≥70 years with resectable gastric cancer (cT1-4a, cN0-2, cM0), diagnosed between 2004 and 2014 were included. Resection rates, administration of chemotherapy (irrespective of surgery), and relative survival within a country according to stage were determined. Results: Overall, 6698 patients were included. The percentage of operated patients was highest in Belgium and lowest in Sweden for both stage II (74% versus 56%) and stage III disease (57% versus 25%). For stage III, chemotherapy administration was highest in Belgium (44%) and lowest in Sweden (2%). Three year relative survival for stage I, II, and III disease in Belgium was 67.8% (95% CI:62.8–72.6), 41.2% (95% CI:37.3–45.2), 17.8% (95% CI:12.5–24.0), compared with 56.7% (95% CI:51.5–61.7), 31.3% (95% CI:27.6–35.2), 8.2% (95% CI:4.4–13.4) in Sweden. There were no significant differences in treatment strategies of patients with stage I disease. Conclusion: Substantial treatment differences are observed across North European countries for patients with stages II and III resectable gastric cancer aged 70 years or older. In the present comparison, treatment strategies with a higher proportion of patients undergoing surgery seemed to be associated with higher survival rates for patients with stages II or III disease.